About inefficiency of personnel policy in health care of russia - V. M. Chernyshev; M. N. Voevoda; I. F. Mingazov (Сибирский научный медицинский журнал, 2020)
The shortage of medical personnel, primarily in the district service and rural health care, the insufficient effectiveness of measures taken by the state to solve the personnel problem («presidential» allowance for the district service, the program «Zemsky doctor», etc.) indicate the insolvency of personnel policy in the industry. The state spending huge budgetary funds for training specialists deprived itself of the right to use them where they are urgently needed. The desire to improve the quality of training of medical students on the basis of accession to the Bologna agreement did not give the desired result. The availability of medical care is also limited by the fact that in the general structure of medical specialties, the number of doctors of clinical specialties, i.e. those who directly work with patients is significantly lower than in the EU and their share continues to decline. All of the above suggests that the Ministry of Health has no clear idea about the issue of personnel, is not formed the system able to solve it, which must include: career counseling -training - public distribution trained on a budgetary basis - professional development - career growth. The state and the leadership of the regions should create favorable conditions for work and life, attracting specialists, as well as interesting them in long-term work at the place of distribution. On the basis of the Soviet experience in the organization of personnel work in health care, best practice of other countries, the authors propose measures in the medical personnel training improvement, in attracting and long-term interest in their work in «problem» positions (district service, rural health care, etc.).